Transcription of alpha- and beta-tubulin genes in vitro in isolated Chlamydomonas reinhardi nuclei (The Rockefeller University Press, 1984)
Removal of the flagella of Chlamydomonas results in increases in both flagellar protein synthesis and tubulin messenger RNA accumulation. These observations led us to examine whether flagellar protein gene sequences are transcribed differentially in nuclei isolated before and after deflagellation. A nuclear isolation protocol was developed using the cell wall-less strain of Chlamydomonas, CW 15, after cell lysis with 0.5% Nonidet P-40. Transcriptional activity of isolated nuclei was determined by incorporating [32P]UTP into TCA-precipitable and phenol- extractable RNA, and by hybridizing newly transcribed RNA to complementary DNA clones containing alpha- and beta-tubulin sequences. Nuclei from deflagellated cells are more active in transcribing sequences that hybridize with alpha- and beta-tubulin complementary DNA probes than are nuclei from nondeflagellated cells. In addition, while total [32P]UTP incorporation is inhibited 45% by alpha-amanitin concentrations of 1.0 micrograms/ml, tubulin RNA synthesis in this system is completely inhibited by this concentration of alpha-amanitin. This demonstration of differential transcription in nuclei before and after cell deflagellation provides the means to study in vitro the mechanisms that signal and regulate flagellar protein gene activity.